Haemtological Parameters of Residents of Offa, KWARA State - Ojulari, Lekan Sheriff; Abubakar, Kabir Taiye; Owoyele, Bamidele Victor (Bangladesh Journal of Medical Science, 2013)
Objectives: This study aims to study some hematologic parameters, here, the packed cell volume (PCV), the red blood cell (RBC) count, hemoglobin concentration (HC) and white blood cell (WBC) count in residents of Offa in Kwara state, Nigeria. Methods: Blood samples of healthy male and female Offa indigenes were analyzed for RBC count, PCV, HC and WBC count. Results: The mean HC was 14.6 and 13.71 g/dl of blood, for both males and females respectively, while the mean PCV was 43.1% and 40.4% for both males and females, respectively. The mean RBC count for males was 5.45 x 166 cells per mm3 while that of females was 4.55 x 106 / mm3. Conclusion: All values investigated were lower than that for Caucasians. The probable causes of the differences between the above values as compared to those of the western world were also discussed. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 180-185 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14947